Is a fatigue index a worthwhile measure of repeated sprint ability? - Oliver, J. L. (Journal of Science and Medicine in Sport, 2009)
The purpose of this opinion piece is to consider the usefulness of fatigue measures when describing performance in repeated sprint tests. The reliability of different methods of calculating fatigue is discussed and an explanation for the large variability explained. Essentially the mathematical procedures involved in calculating fatigue levels from a small drop-off in performance will always result in an unreliable measure. Consequently, the use of a fatigue index or percentage decrement score to describe repeated sprint ability may be questioned.